2008
DOI: 10.1017/s0954579408000242
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association between infant disorganized attachment and childhood posttraumatic stress symptoms

Abstract: The purpose of this study was to evaluate whether children with a history of disorganized attachment in infancy were more likely than children without a history of disorganized attachment to exhibit symptoms of posttraumatic stress disorder (PTSD) at school age following trauma exposure. The sample consisted of 78 8.5-year-old children from a larger, ongoing prospective study evaluating the effects of intrauterine cocaine exposure (IUCE) on children's growth and development from birth to adolescence. At the 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 54 publications
2
35
1
Order By: Relevance
“…Attachment disorganization, as represented by an AAP classification of "Unresolved", showed a statistically significant, moderate association with symptomatology in this sample. This finding is consistent with previous research linking attachment disorganization and trauma-related symptoms in various samples [17,21,42]. Attachment status was also meaningfully linked to cognitive efficiency, with unresolved adolescents showing more impairment in working memory specifically than their organized counterparts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Attachment disorganization, as represented by an AAP classification of "Unresolved", showed a statistically significant, moderate association with symptomatology in this sample. This finding is consistent with previous research linking attachment disorganization and trauma-related symptoms in various samples [17,21,42]. Attachment status was also meaningfully linked to cognitive efficiency, with unresolved adolescents showing more impairment in working memory specifically than their organized counterparts.…”
Section: Discussionsupporting
confidence: 91%
“…In their prospective study of 168 children into early adulthood, Ogawa et al [17] found that both disorganized and avoidant patterns of attachment predicted dissociative symptoms in their sample, although the disorganized pattern showed more consistent association with dissociation, one of the core features of Post-Traumatic Stress Disorder, particularly in late adolescence/early adulthood. Another longitudinal study, by McDonald and co-authors [21], examined the association between attachment status at 12 months and post-traumatic stress disorder symptoms roughly 7 years later. The authors found that disorganized attachment uniquely predicted avoidance-related post-traumatic symptoms in their sample.…”
Section: Attachment Disorganization and Trauma-related Symptomsmentioning
confidence: 99%
“…Further novel to the current study was an assessment of the concurrent validity of the CARTS in relation to experiences of attachment in adult romantic relationships, where the literature suggests that experiences of childhood attachment predict future adult romantic attachment (Hesse & Main, 2000; Kochendorfer & Kerns, 2017; MacDonald et al, 2008). In the present study, select correlations between CARTS Mother ratings and responses to the ECR-R were significant, in particular in the association with concurrent anxious romantic attachment.…”
Section: Discussionmentioning
confidence: 98%
“…The fearful disorganized behaviors also typically appear following one of the brief separations, during that moment of reunion when the securely attached child approaches readily and is comforted promptly. Attachment disorganization in the early infant-mother relationship has been associated prospectively in longitudinal work and meta-analytic summaries of the findings with later childhood problem behaviors, especially aggression [13], post-traumatic stress disorder (PTSD) symptoms in the school years [14], and dissociation problems in adolescence [15].…”
Section: Introductionmentioning
confidence: 99%